2017
DOI: 10.3390/ma10111229
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid One-Step Process for Fabrication of Biomimetic Superhydrophobic Surfaces by Pulse Electrodeposition

Abstract: Inspired by some typical plants such as lotus leaves, superhydrophobic surfaces are commonly prepared by a combination of low surface energy materials and hierarchical micro/nano structures. In this work, superhydrophobic surfaces on copper substrates were prepared by a rapid, facile one-step pulse electrodepositing process, with different duty ratios in an electrolyte containing lanthanum chloride (LaCl3·6H2O), myristic acid (CH3(CH2)12COOH), and ethanol. The equivalent electrolytic time was only 10 min. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Compared with the traditional continuous DC electrodeposition, many characteristics of pulse electrodeposition make it especially suitable for the preparation of superhydrophobic coatings. It can not only comprehensively control the crystal growth rate and morphology of deposited materials through parameters such as voltage, current, frequency, and duty cycle but can also rapidly refresh the ions, which is suitable for preparing superhydrophobic films with high surface quality. , However, to our knowledge, few previous studies have been reported to develop a nonfluorinated superhydrophobic metal foam for effective oil/water separation via a facile, nonfluorinated, and economical pulse electrochemical deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional continuous DC electrodeposition, many characteristics of pulse electrodeposition make it especially suitable for the preparation of superhydrophobic coatings. It can not only comprehensively control the crystal growth rate and morphology of deposited materials through parameters such as voltage, current, frequency, and duty cycle but can also rapidly refresh the ions, which is suitable for preparing superhydrophobic films with high surface quality. , However, to our knowledge, few previous studies have been reported to develop a nonfluorinated superhydrophobic metal foam for effective oil/water separation via a facile, nonfluorinated, and economical pulse electrochemical deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is a part of DC electrodeposition, where there are distinctive pulses with off‐time intervals between deposition steps. So, on and off time durations which define the duty ratio, the ratio of the on‐time to the total period, govern the deposits properties …”
Section: Introductionmentioning
confidence: 99%
“…The duty ratio has a considerable influence on the nucleation, growth and migration rates of the crystals on the sample, which finally designs the surface morphology . It is reported that the aggregated cations near the cathode are adsorbed on it during the on‐time ,,,,.…”
Section: Introductionmentioning
confidence: 99%
“…A facile strategy of improving surface hydrophobicity to superhydrophobicity of PPXC film is important in industrial applications of PPXC film [ 15 , 16 , 17 ]. The surface wettability can be tuned by changing surface morphologies or surface chemical compositions [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Regulation of surface morphologies had been extensively explored for pattern structures [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], which could be obtained by printing [ 35 , 36 ], self-assembly of block copolymer [ 37 ], and femtosecond laser structuring [ 38 ].…”
Section: Introductionmentioning
confidence: 99%